Are Gynaecologists underutilising the open access technique for laparoscopic surgery? - Dhillon, Atmajit Singh; Sood, Sandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Open access technique for laparoscopic surgery is used by the surgeons routinely, for gaining intraabdominal access safely, but is somehow underutilised by gynaecologists. The most important and dangerous part of laparoscopic surgery is while gaining access to the abdominal cavity, especially in the obese, thin and in patients with previous abdominal scars. Various access techniques have been described including Hasson and Fielding technique, transvaginal or transuterine insufflation, alternative sites for introducing Veress needle abdominally and insufflations with an optical trocar. Open access technique can minimize visceral and vascular injuries and ensures quick and easy intra-abdominal access. Methods: 250 patients were taken up for laparoscopic surgery at tertiary care service hospitals for open access technique for laparoscopic surgery for a variety of indications. The spectrum of patients ranged from thin, obese, single and multiple transverse scars Results: A total of 250 patients, were taken up for laparoscopic surgery with the open access method successfully. The median age of the patients was 32 years, there were 77 patients (31%), with previous transverse laparotomy incisions. Median time for access was 100 seconds, and in 102 patients, there was prolonged access time ranging from 150-300 seconds, 37 (36%) of these patients were those with previous multiple transverse laparotomies and 65 (64%), patients were obese. There were no intra-abdominal organ or vascular injuries. Skin incisions healed well. Conclusions: This study describes the open access technique in patients, with transverse laparotomy scars and especially useful in thin and obese women, and where the chances of vascular and visceral injuries can be high while gaining intra - abdominal access. It is safe, effective, easy to learn and requires minimal instrumentation and can be used in the vast majority of the gynaecological cases.